Keys for Identification of Plant Remains in Faecal Matter of Ungulates - Sharma, R. D. (Indian Forester, 1996)
This paper presents keys for identification of plant remains in faecal matter of ungulates. These Keys are useful in identification of indigestible or undigested food parts which are eliminated out from the animal body along with faecal matter. Main Key is based on trichornes and for cross checking the main key, supplementary keys have been based on features like crystals, epidermal cell characteristics, stomatal characteristics, scle ridcs, structural pecularities in fruit and seed tissues that are present in faecal matter of ungulates.